2000
DOI: 10.3171/spi.2000.93.2.0194
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgically managed patients with degenerative spondylolisthesis: a 10- to 18-year follow-up study

Abstract: Object. Controversy exists concerning the indications for surgery and choice of surgical procedure for patients with degenerative spondylolisthesis. The goals of this study were to determine the clinical course of nonsurgically managed patients with degenerative spondylolisthesis as well as the indications for surgery. Methods. A total of 145 nonsurgically managed patients with deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 18 publications
(21 reference statements)
4
62
1
5
Order By: Relevance
“…Only 10-15% of patients seeking treatment eventually will have surgery [45]. In a long term follow-up study of 145 nonsurgically managed patients [38] with DS progression of vertebral slippage was observed in 34% of patients. There was no correlation between changes in clinical symptoms and progression of spondylolisthesis.…”
Section: Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…Only 10-15% of patients seeking treatment eventually will have surgery [45]. In a long term follow-up study of 145 nonsurgically managed patients [38] with DS progression of vertebral slippage was observed in 34% of patients. There was no correlation between changes in clinical symptoms and progression of spondylolisthesis.…”
Section: Prognosismentioning
confidence: 99%
“…The study of the natural history [38] showed that back pain improved as the disc space was collapsed and progression of the slippage occurred only in 34% of the cases. Seventy-six percent of the patients who were initially neurologically intact did not deteriorate over time and these patients may be treated conservatively.…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With a follow-up of 10 years they found that DS progressed in 34% of the cases but there was no correlation between progression of the slip and clinical symptoms (Matsunaga et al 2000). In addition, no further progression of the slip was observed in the segments with collapsed discs and the back pain improved over time as the discs collapsed (Matsunaga et al 2000).…”
Section: The Natural History Of Spinal Stenosismentioning
confidence: 95%
“…The natural course of untreated DS has been studied by Matsunaga et al (2000). With a follow-up of 10 years they found that DS progressed in 34% of the cases but there was no correlation between progression of the slip and clinical symptoms (Matsunaga et al 2000).…”
Section: The Natural History Of Spinal Stenosismentioning
confidence: 99%